Intermedialità e sinmedialità nella videoarte contemporanea: Robert Cahen e Pierre Boulez - Raffaele Pozzi (LED Edizioni Universitarie, 2023)
Intermediality and Sinmediality in Contemporary Video Art: Robert Cahen and Pierre Boulez The French video artist Robert Cahen (Valence, 1945), member of the Groupe de Recherches Musicales (GRM) founded in Paris in 1958 by André Schaeffer, begun to apply to images the experimental techniques of the so-called «musique concrète» in the early Seventies. Since his first video («L'invitation au voyage», 1972) Cahen manipulates images like sounds and explores the dimension of time perception. Inspired by the complex, fluid motions of sounds in space and by the Schaeffer's theory and practice of the «écoute réduite», he develops a visual style deeply influenced by a musical conception of time. The concept of time is central in both the Cahen's works devoted to Pierre Boulez's music and conducting: the film «Boulez-Répons» (1985) and the video installation «Le Maître du temps. Pierre Boulez dirige Mémoriale» (2011). The article presents and analyzes the original audiovisual language and aesthetic meaning of both works according to the concept of «intermediality» and «sinmediality» in contemporary video art.